The social composition of Italian co-operatives: Historical evolution and analysis of political and economic reasons - Michele Bianchi (The Journal of European Economic History (JEEH), 2021)
Since the 19th century, co-operatives have served their members through a system of mutual benefits between members and organisations, aggregating homogeneous stakeholders. What are the reasons for this change? This study reviews the relevant literature, taking an historical institutional approach to the evolution of the social composition of co-operatives. More generally, the article shows the reciprocal influence between organisations and society, framing the complex socio-political system within which co-operatives have evolved and influenced Italian society.
Keywords: 330